PENGARUH PREFERENSI KONSUMEN DAN HARGA TERHADAP MINAT PEMBELIAN PRODUK KERIPIK TEMPE SAGU PADA UMKM CAMILAN RNB YOGYAKARTA - Eti Endiarti; Pujiati Utami; Dumasari Dumasari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the influence of consumer preferences and pricing on purchase intention for Keripik Tempe Sagu products at UMKM Camilan RNB in Yogyakarta. The research employs a descriptive quantitative method involving 60 respondents who are consumers of the business, with data collected through questionnaires. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. The results indicate that partially, price has a positive and significant effect on purchase intention, while consumer preferences do not show a significant effect. However, simultaneously, both variables have a positive and significant influence on purchase intention. The contribution of consumer preferences and price is 41.1%, while the remaining 58.9% is influenced by other variables outside the model. The findings imply that the business should maintain competitive pricing strategies while still considering factors shaping consumer preferences, especially among young consumers with limited purchasing power.